Music performance self-efficacy scale development study - Gülle, Alican; Akay, Cenk (Intelektual Pustaka Media Utama, 2026)
In this study, it was aimed to develop a measurement tool to measure middle school students’ music performance self-efficacy. There were 2 separate research groups in the study, 447 observation sets in the first research group and 351 observation sets in the second research group. Exploratory factor analysis (EFA) was conducted with the first research group and confirmatory factor analysis (CFA) with the second research group. In the study, a factor structure consisting of 5 factors, explaining 59.9% of the total variance and 27 items with factor loadings ranging from 0.365 to 0.770 was obtained. As a result of CFA, it was determined that the standardized values ranged between 0.59 and 0.84 and the fit indices were within the model fit criteria. The cronbach alpha value obtained for the entire factor structure was 0.922. When the sub-factors were analysed, it was found that the Cronbach alpha value of the first factor was 0.904, the second factor was 0.815, the third factor was 0.763, the fourth factor was 0.815, and the fifth factor was 0.760. As a result of all findings, it was revealed that the developed scale is a valid and reliable measurement tool.